Prinzipien der Sarkomchirurgie - Jakob, Jens; Hohenberger, Peter (Der Pathologe, 2019)
Soft-tissue sarcomas are rare malignant tumors. Surgery remains the most important treatment modality. Neoadjuvant and/or adjuvant chemo- and radiotherapy may be administered to improve the local and systemic outcome. Advances in oncological and reconstructive surgery, combined with the use of multimodal therapies, have made mutilating surgery rare events in extremity sarcomas. In retroperitoneal sarcomas, local recurrences are life-threatening events and multivisceral resection has become the standard surgical procedure. The subjects of this review are diagnostics, multimodal therapy, and resection strategy from a surgical point of view.